Pulsewidth switchable, wavelength tuneable ultrafast fiber laser mode-locked by carbon nanotubes - Wang,F; Popa,D; Sun,Z; Hasan,T; Torrisi,F; Going,R; Ferrari,AC (2012 IEEE Photonics Conference, IPC 2012, 2012)
Employing a nanotube-based saturable absorber, we demonstrate a continuously tunable (1533-1563nm) ultrafast fiber laser, with output pulsewidth switchable between picosecond (1.2 ps) and femtosecond (610 fs) regimes. © 2012 IEEE.